Reclaiming development - Chang, Ha-Joon. (Dhaka, 2004)
There is no alternative - to neo-liberal economics, Americanisation and globalisation - remains the driving assumption within the international development policy establishment. Ha-Joon Chang and Ilene Grabel explain the main assertions of this dominant school. They combine data, a devastating economic logic, and an analysis of the historical experiences of leading Western and East Asian economies, to question the validity of the neo-liberal development model. They then set out practical alternatives in the key areas: trade and industrial policy; privatisation; intellectual property rights; external borrowing; investment; financial regulation; exchange rates, monetary policy, government revenue and expenditure. The most useful proposals that have emerged around the world are combined with some innovative measures of their own, in an empowering and accessible book.
Keywords: Economic policy